Positionen : Israel : collection Höcherl/Asperger. - W. Asperger Gallery AG, Zug (München : Verlag Dr.Rainer Höcherl, 1992)
Bar-El, Ido ; Cohen Gan, Pinchas ; Garbuz, Yair ; Gershuni, Moshe ; Getter, Tamar ; Klasmer, Gabi ; Kupferman, Moshe ; Lavie, Raffi ; Levin, Yehudit ; Nikel, Lea ; Pichhadze, Meir ; Rikman, Tamara ; Shemi, Yehiel ; Uri, Aviva
Positionen : Israel, collection Höcherl/Asperger, W. Asperger Gallery AG, Zug, 1992
boek